Penilaian para ulama Islam terhadap metode tafsiran aliran Salafiyyah kontemporari ke atas ayat Sifat - Norasimah Haji Omar; Mazlan Ibrahim (Penerbit Universiti Kebangsaan Malaysia, 2019)
The emergence of contemporary Salafi school in the mainstream Muslims is intended to make the Ahl al-Salaf as the primary models of faith and to return the related problems of faith according to the path taken by the companions and tabi‘in, which had been quoted only from the al-Quran and al-Sunnah. These stances left great influences on their method of interpretations upon the Quranic verses including the Ayat al-Sifat (verses on Divine Attributes) and condemning others out of the Ahl al-Sunnah wa al-Jama‘ah. Therefore this research is intended to identify responses of Muslim figures and scholars against the Contemporary Salafi School’s stances and their method of interpretations on Ayat al-Sifat. In addition, this research is also intended to explain the views of the majority of scholars on the conceptual and methods of interpretation of Ayat al-Sifat adopted by the Ahl al- Sunnah wa al-Jama‘ah. The paper is produced with the synthesization of content analysis that focuses on published works by selected Contemporary Salafi school figures and other muslim scholars and also relevant contemporary researchers in relation to these issues of Ayat al-Sifat and its methods of interpretations. The results of this research found that most scholars do not accept the method of literal interpretations on Ayat al-Sifat proclaimed by Contemporary Salafi School due to the existence of two catogeries of the Quranic verses, which are known as Wadih Jalli and Khafi Mutashabih or Mutashabih al-Sifat. In certain cases, the method of 'ta’wil' is highly needed to clarify the meaning of Ayat al-Sifat so easily understood by human intellect and at the same time to purify Allah the almighty from signs of weaknesses and resemblance. The extreme acts from Contemporary Salafi School in defending their methods of interpretations make them an 'exclusive' school which separated themselves from other muslims, and limit the diversity of the methods of interpretations enabled by the majority of mufassirin.